The Non-Profit Nature in Doubt in The Operation of Foundations - Panjaitan, Tulus Abadi; Gultom, Muhammad Arifin; Ramlan, Ramlan (JURNAL AKTA, 2024)
This research aims to analyze the legal aspects of business activities carried out by foundations, especially in the education and health sectors, which should be based on non-profit principles. Foundations, as legal entities with separated wealth, have the authority to participate in business activities to support the achievement of their goals in the social, religious and humanitarian fields. However, foundations are required to adhere to the non-profit principle and not pursue personal gain. The writing method in this research uses a normative juridical approach with descriptive analysis of laws and practices related to foundations. The novelty of this research lies in the legal study of foundations that establish or operate commercial businesses, particularly in the education and health sectors, which often contradict the basic principles of foundations as non-profit entities. Although foundations can generate economic benefits from their business activities, this raises serious legal challenges regarding the foundation's legal status. This research concludes that foundations that are more focused on economic and commercial objectives may be declared in violation of their founding principles and potentially receive legal sanctions, including dissolution, if proven to conduct activities that prioritize commercial aspects over their social mission. As such, this research provides an important contribution in understanding the legal consequences for foundations that deviate from the social, religious, or humanitarian purposes for which they were established.